2017
DOI: 10.1016/j.cellimm.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian propolis promotes immunomodulation on human cells from American Tegumentar Leishmaniasis patients and healthy donors infected with L. braziliensis

Abstract: American Tegumentar Leishmaniasis (ATL) is an infectious disease caused by Leishmania parasites with ineffective treatment. The properties of propolis have been studied in different experimental studies, however, few works have investigated the effects of propolis on human-derived peripheral blood mononuclear cells (PBMC) in leishmaniasis models. Thus, we investigate the immunomodulatory effects of propolis treatment on PBMC from ATL patients and on PBMC from healthy donors infected with Leishmania braziliensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…TGF- β and IL-10 are known to play an important role in macrophage deactivation, leading to increased parasite load in experimental models of L. (L) amazonensis , L. (V) braziliensis , and L. (L) major infection [59–62]. In addition, dos Santos Thomazelli et al [63] reported an immunomodulatory effect by treatment with hydroalcoholic propolis extract on PBMCs from CL patients, as well as on PBMCs from healthy donors infected or not with Leishmania (V) braziliensis , in which the extract was shown to increase IL-4 and IL-17, while decreasing IL-10 levels.…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β and IL-10 are known to play an important role in macrophage deactivation, leading to increased parasite load in experimental models of L. (L) amazonensis , L. (V) braziliensis , and L. (L) major infection [59–62]. In addition, dos Santos Thomazelli et al [63] reported an immunomodulatory effect by treatment with hydroalcoholic propolis extract on PBMCs from CL patients, as well as on PBMCs from healthy donors infected or not with Leishmania (V) braziliensis , in which the extract was shown to increase IL-4 and IL-17, while decreasing IL-10 levels.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the immunomodulatory properties of Brazilian propolis was investigated in human-derived peripheral blood mononuclear cells (PBMC) isolated from L. braziliensis infected patients. This study found that in both healthy and infected donors, propolis was able to increase the levels of IL-4 and IL-17 while decreasing IL-10, showing an overall decrease in inflammation which could promote the control of the parasites ( Dos Santos Thomazelli et al, 2017 ).…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Lmentioning
confidence: 95%
“…(2) The alteration of angiogenesis in the affected tissue [236,238]; (3) Stimulation of immunomodulatory effects, by influencing the production of interferon-γ, tumor necrosis factor α, IL-1, IL-4 and IL-17 [239][240][241]; (4) Induction of apoptosis-like mechanisms in parasites [236]; (5) Membrane disruption in parasites [242].…”
Section: Antiparasitic Potential Of Bee Productsmentioning
confidence: 99%